The effect of the plant density on the yield of flint corn in conditions of the Eastern part of the Steppe of Ukraine - Маслійов, С. В. (Scientific Progress & Innovations, 2016)
The results of field experiments of the plant density effect on the yield of flint corn grain in conditions of the Eastern part of the Steppe of Ukraine have been given. Comparative data on the dynamics of flint corn growth depending on the sowing term and plant density have been presented. The growing season of plants and the elements of the yield structure have been analyzed. The data on the yield of flint corn grain depending on the plant density have been given. The optimum plant density for middle-early hybrid Kremin’ 200 SV in conditions of the Eastern part of the Steppe of Ukraine has been recommended.